THE IMPORTANCE OF CULTURAL UNDERSTANDING IN TRANSLATION - Barchinoy, Bakhronova (Journal of Higher Education and Academic Advancement, 2024)
This article talks about the importance of cultural understanding in translation and gives some important aspects of cultural communication in translation.